2009
DOI: 10.1093/schbul/sbp141
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia and Its Treatment

Abstract: Psychiatric diagnoses are currently categorized on a syndromic basis. The syndrome of catatonia, however, remains in a diagnostic limbo, acknowledged predominantly as a subtype of schizophrenia. Yet, catatonia is present in about 10% of acutely ill psychiatry patients, only a minority of whom have schizophrenia. Among those with comorbid affective disorders, who comprise the largest subgroup of catatonic patients, the catatonic signs typically resolve dramatically and completely with benzodiazepine therapy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
156
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(183 citation statements)
references
References 19 publications
7
156
1
9
Order By: Relevance
“…Benzodiazepines at high doses and ECT have routinely beneficial effects in treating catatonia, as has been described by others in the literature. 5,8 For patients with malignant catatonia, investigations have shown that daily, bilateral ECT during the first week is most effective. 4,8 We also note that no significant difference in short-term outcome was observed between ECT, sham ECT and nonconvulsive stimulation in catatonia associated with chronic schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Benzodiazepines at high doses and ECT have routinely beneficial effects in treating catatonia, as has been described by others in the literature. 5,8 For patients with malignant catatonia, investigations have shown that daily, bilateral ECT during the first week is most effective. 4,8 We also note that no significant difference in short-term outcome was observed between ECT, sham ECT and nonconvulsive stimulation in catatonia associated with chronic schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,3 Recent literature suggests a 10-15% prevalence of catatonia among acute psychiatric inpatients. 4,5 While classic cases of catatonia are easily recognized, subtler signs and symptoms of catatonia are more prevalent and their recognition is more challenging for clinicians. 6,7 Catatonic presentations are often overlooked in the context of psychotic and/or mood episodes but the treatment for catatonia can be very different than that for psychotic and mood disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In either case, some families may not be able to adhere to the proscribed schedule of ECT making it less effective. In cases where there is a documented primary psychotic disorder, combination of secondgeneration antipsychotics and lorazepam may be recommended with careful monitoring for signs of MC or NMS [20].…”
Section: Risk Versus Benefit Of Using Ect In Patients With Catatoniamentioning
confidence: 99%
“…Certain patient populations, such as the elderly, those with obstructive sleep apnea or history of paradoxical responses to BZPs, may not tolerate higher dosage of lorazepam or another agent from this class; therefore, ECT may be the best treatment option in these situations [20].…”
Section: Introductionmentioning
confidence: 99%